KONVERGENSI NUSANTARA TV DALAM MENGEMBANGKAN MEDIA DIGITAL - Falasifah, Falasifah; Rinaldi, Aldi; Widyaya, Ismoko; Miftahul Jannah, Selfie (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
The Indonesian media industry has experienced rapid growth, with numerous new television stations emerging. Nusantara TV, as one of these new entrants, faces significant challenges in competing with well-established television stations. The rise of digital media has shifted viewer preferences, with many individuals opting to consume content on platforms like YouTube and social media. In this digital age, the concept of media convergence is vital. Convergence refers to the integration of various media platforms to achieve a common goal. To remain relevant and competitive, Nusantara TV must embrace this concept. This study employs a qualitative descriptive method, focusing on Nusantara TV's social media platforms, including YouTube and Instagram, as well as its special events. Data was collected through interviews, observations, and documentation. Nusantara TV has successfully leveraged YouTube and Instagram to create a more interactive and responsive platform for its audience. Additionally, the television station has organized special events, such as Pesona Nusantara, to promote its brand and engage with its audience. In conclusion, Nusantara TV's convergence with social media and the organization of special events have significantly expanded its audience reach, enhanced interaction with viewers, and generated additional revenue.